Investigation of the repeatability of residual stress measurements using X-ray diffraction on cold extruded cups - Friedlein, Manuel; Hoffmann, Dominik; Knaps, Michael; Merklein, Marion (Materials Research Proceedings, 2025)
Cold extrusion is considered a sustainable production process as it is highly material-efficient. In order to further increase sustainability, the aim is to produce near-net-shape components, which leads to more complex geometries and thinner wall thicknesses. Residual stresses are taking on an increasingly important role here, as they have a strong influence on operating behavior and dimensional accuracy. The stresses can lead to distortion, especially when processing extruded components. One method for measuring residual stresses is X-ray diffractometry, which, however, tends to have high fluctuations in the measurement. To ensure that interactions between residual stress and distortion can be reliably detected, the repeatability of measurements on forward extrusion cups is analyzed.
CRIS-Team Scopus Importer:2025-06-27
Keywords: Cold Forming; Cup Forward Extrusion; Residual Stresses; X-Ray Diffraction